Maldives-Assessment Letter for the Asian Development Bank and the World Bank. (Policy Papers; Policy Paper ;, 2009)
The global crisis has hit the Maldivian economy hard; combined with an unsustainable fiscal expansion, it has led to a large fiscal deficit and severe balance of payments pressures. The authorities are committed to a strong policy adjustment program, and have requested IMF financial support for their program.